2008
DOI: 10.1523/jneurosci.2645-08.2008
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Excitation of Corticothalamic Neurons by Nicotinic Acetylcholine Receptors

Abstract: In this study, we show robust nicotinic excitation of pyramidal neurons in layer VI of prefrontal cortex. This layer contains the corticothalamic neurons, which gate thalamic activity and play a critical role in attention. Our experiments tested nicotinic excitation across postnatal development, using whole-cell recordings in prefrontal brain slices from rats. These experiments showed that layer VI neurons have peak nicotinic currents during the first postnatal month, a time period of intensive cortical develo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
129
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(148 citation statements)
references
References 56 publications
(79 reference statements)
15
129
1
Order By: Relevance
“…Previous studies have shown that micro-injection or bath application of nicotine can increase the excitability of corticothalamic (Kassam et al, 2008), entorhinal (Tu et al, 2009) and prefrontal cortical neurons (Vidal and Changeux, 1993;Lambe et al, 2003). However as noted previously, nicotine can also depolarize inhibitory cortical neurons (Couey et al, 2007).…”
Section: Subcellular Distribution Of ␣4* Nachrs In Somatosensory Cortexmentioning
confidence: 71%
“…Previous studies have shown that micro-injection or bath application of nicotine can increase the excitability of corticothalamic (Kassam et al, 2008), entorhinal (Tu et al, 2009) and prefrontal cortical neurons (Vidal and Changeux, 1993;Lambe et al, 2003). However as noted previously, nicotine can also depolarize inhibitory cortical neurons (Couey et al, 2007).…”
Section: Subcellular Distribution Of ␣4* Nachrs In Somatosensory Cortexmentioning
confidence: 71%
“…While so many aspects of pyramidal cell function are well described, nAChRs are rarely found on pyramidal cells in the cortex [55,75]. A recent study has found nAChRs on layer VI pyramidal cells [71] ( Figure 1). This specific population represents pyramidal cells projecting back to the thalamus.…”
Section: Nicotinic Modulation Of Thalamocortical Communicationmentioning
confidence: 98%
“…In the rat PFC, there are strong developmental changes in nicotinic signalling of pyramidal neurons in layer VI. The nicotinic currents recorded from these neurons mediated by α5-containing nAChRs peak at postnatal week 3 [71]. In human brain, the levels of nAChRs also show regionspecific changes in development.…”
Section: Cortical Development and Nachrsmentioning
confidence: 99%
See 2 more Smart Citations